2011
DOI: 10.1128/jvi.00146-11
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Promotes Hepatic Gluconeogenesis through an NS5A-Mediated, FoxO1-Dependent Pathway

Abstract: Chronic hepatitis C virus (HCV) infection is often associated with type 2 diabetes.However, the precise mechanism underlying this association is still unclear. Here, using Huh-7.5 cells either harboring HCV-1b RNA replicons or infected with HCV-2a, we showed that HCV transcriptionally upregulated the genes for phosphoenolpyruvate carboxykinase (PEPCK) and glucose 6-phosphatase (G6Pase), the rate-limiting enzymes for hepatic gluconeogenesis. In this way, HCV enhanced the cellular production of glucose 6-phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 74 publications
10
100
0
1
Order By: Relevance
“…FOXOs are also required for lipid homeostasis. 37 HCV infection was shown to contribute to insulin resistance by increased FOXO1 activity, 20,38 and a similar observation has been made for nonalcoholic steatohepatitis. 39 It has more recently been shown that FOXO3 activity is increased by starvation/malnutrition in HCV infection, where it modulates innate immunity signaling.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…FOXOs are also required for lipid homeostasis. 37 HCV infection was shown to contribute to insulin resistance by increased FOXO1 activity, 20,38 and a similar observation has been made for nonalcoholic steatohepatitis. 39 It has more recently been shown that FOXO3 activity is increased by starvation/malnutrition in HCV infection, where it modulates innate immunity signaling.…”
Section: Discussionsupporting
confidence: 57%
“…18 The role of FOXO in injury processes is complex because FOXO transcriptional programs can be either cytoprotective or cytotoxic, and welldocumented examples of both phenomena are numerous. 19 There have been a limited number of reports of the effect of HCV infection on FOXO activity, and these have shown that activation of FOXO1 or FOXO3 by HCV may contribute to insulin resistance 20 and autophagy induction. 21 FOXO3 has also recently been shown to be part of a proapoptotic pathway in human peripheral blood cells.…”
mentioning
confidence: 99%
“…We previously reported that HCV induces JNK activation through increased mitochondrial ROS production (Deng et al, 2011). We therefore tested whether HCV-induced JNK activation contributes to Bax activation.…”
Section: Hcv-induced Jnk Activation Is Involved In Activation and Mitmentioning
confidence: 94%
“…Increasing evidence has suggested that c-Jun NH 2 -terminal kinase (JNK) plays a role in Bax-mediated apoptosis by regulating the function of Bim (Lei & Davis, 2003;Okuno et al, 2004;Putcha et al, 2003). Also, we previously demonstrated that HCV-induced ROS production causes JNK activation, resulting in increased gluconeogenesis (Deng et al, 2011). In the present study, we investigated the possible link between HCV-induced ROS/JNK signalling and Bim/Baxmediated apoptosis using the HCV cell culture system.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation